Cumulative effects of low X-ray doses on some liver function and proteins of diagnostic technicians working in conventional X-rays - Kharman A. Faraj (Zanco Journal of Pure and Applied Sciences, 2021)
Today X-rays are widely used for diagnostic in medicine using different technics such as computed tomography (CT), fluoroscopy and conventional X-ray. During diagnostic procedures the technicians might expose to low X-ray doses especially those who omit radiation protection tools. The aim of the study was to assess liver function and proteins due to the cumulative effects of low X-ray doses on diagnostic technicians through measuring aspartate aminotransferase (AST), alanine aminotransferase (ALT), total proteins, albumin, globulin, serum ferritin (s.ferritin), malondialdehyde (MDA) and glutathione (GSH). Twenty four male diagnostic technicians at Kirkuk hospitals participated, they classified into two groups depending on their working experiences, each group with 12 technicians. Twelve male healthy controls participated to show any alteration of the parameters. The results showed that ALT, AST and s.ferritin increased significantly (p<0.05) for the first group compared to the control while high significant (p<0.001) increasing was recorded for the second group. Total proteins decreased significantly (p<0.05) in the first group and high significant (p<0.001) decreasing in the second group compared with the control group. High significant (p<0.001) decreasing for albumin was recorded in both groups while globulin decreased insignificantly (p>0.05) in the first group and significant (p<0.05) decreases were recorded for the second group. For MDA and GSH high significant (p<0.001) increasing and decreasing respectively, recorded for both groups. The study revealed that low doses of X-ray can change some liver functions and proteins and the number of working years has discernible effects on the cumulative doses in diagnostic technicians.